Pengaruh Budaya Kerja Dan Etos Kerja Terhadap Kinerja Karyawan PT. Pelindo (Persero) Cabang Samarinda - cahyani, Erischa Cahyani; Vera Anitra; Rinda Sandayani Karhab (PROGRAM PASCA SARJANA MAGISTER MANAJEMEN INSTITUT TEKNOLOGI DAN BISNIS ASIA MALANG, 2025)
Abstract This study aims to examine and analyze the influence of work culture and work ethic on employee performance at PT. Pelindo (Persero) Samarinda Branch. Work culture and work ethic are two essential factors believed to contribute significantly to enhancing employee productivity and performance. This research employs a quantitative approach using a survey method, where data were collected through questionnaires distributed to permanent employees of PT. Pelindo (Persero) Samarinda Branch. The data were analyzed using multiple linear regression with the assistance of SPSS software. The results indicate that both work culture and work ethic have a positive and significant effect on employee performance, both partially and simultaneously. A strong organizational culture and a high level of work ethic have proven to improve employee performance outcomes. Based on these findings, the company is encouraged to continue strengthening the implementation of positive work culture values and fostering employee work ethic through training, coaching, and appropriate reward systems to sustainably enhance performance.